(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
A 28-year-old male was admitted in the emergency wing of Sri Guru Ram Das Institute of Medical Sciences and Research with alleged history of assault for about 24 h. At the time of admission, patient was semiconscious; he could recognised his father but was not oriented to time and place. On further medico-legal examination, clinical examination and laboratory investigation of the case opium was detected in his urine along with injury report, on the different parts of the body. The medico-legal examination, police investigation and laboratory investigation supported the use of opium poisoning for torture/revenge proposes and after discussion the case was registered under section 328 IPC.